Camptodontornis gen. nov., a replacement name for the bird genus Camptodontus Li, Gong, Zhang, Yang, and Hou, 2010, a junior homonym of Camptodontus Dejean, 1826 - Demirjian, Vahe (Zootaxa, 2019)
Camptodontus yangi Li, Gong, Zhang, Yang, and Hou, 2010 was erected for a complete enantiornithine bird skeleton from the Early Cretaceous Jiufotang Formation in Liaoning, northeastern China (Li et al. 2010). However, the genus name Camptodontus is a junior homonym of the beetle genus Camptodontus Dejean, 1826. Under Article 23.1 of the International Code of Zoological Nomenclature (ICZN 1999) Dejean’s 1826 name has priority.